Peptide Loading on MHC Class I Molecules of Tumor Cells - Loredana Cifaldi; Franco Locatelli; Doriana Fruci (Bio-Protocol, 2016)
MHC class I molecules present peptides to cytotoxic T cells allowing the immune system to scan for intracellular pathogens and mutated proteins. The generation of antigenic peptides is a multistep process that ends in the endoplasmic reticulum (ER). Only peptides with the right length and sequence will bind nascent MHC class I molecules in the ER. This protocol allows for detachment of the endogenous peptides bound to MHC class I molecules by preserving them for the binding of high affinity synthetic peptides. The complete dissociation of endogenous peptides by mild acid treatment as well as the binding of synthetic peptides to MHC class I molecules will be evaluated measuring HLA class I molecules express on the cell surface by flow cytometry. The mouse antibody W6/32 which recognizes β2m associated HLA-A, -B, -C, -E and -G heavy chains is suitable for this propose. Any tumor cell line that expresses surface HLA class I molecules is suitable for the assay. Another important aspect is to know the HLA class I typing of tumor cell line to allow selection of the known high affinity peptides.